Multiresistance of Staphylococcus xylosus and Staphylococcus equorum from Slovak Bryndza cheese - Mikulášová, Mária; Valáriková, Jana; Dušinský, Roman; Chovanová, Romana; Belicová, Anna (Folia microbiologica, 2014)
Staphylococcus xylosus, Staphylococcus equorum, and Staphylococcus epidermidis strains were isolated from Bryndza cheese and identified using PCR method. The antimicrobial susceptibility of these strains was assessed using disc diffusion method and broth microdilution method. The highest percentage of resistance was detected for ampicillin and oxacillin, and in contrary, isolates were susceptible or intermediate resistant to ciprofloxacin and chloramphenicol. Fourteen of the S. xylosus isolates (45%) and eleven of the S. equorum isolates (41%) exhibited multidrug resistance. None of the S. epidermidis isolate was multiresistant. The phenotypic resistance to oxacillin was verified by PCR amplification of the gene mecA.
Keywords: Food Microbiology; potravinářská mikrobiologie; Microbial Sensitivity Tests; sýr; Staphylococcus; Methicillin Resistance; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; Drug Resistance, Bacterial; Cheese; bakteriální léková rezistence; rezistence na methicilin